2016
DOI: 10.1111/pce.12742
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal P3 protein AtP3B of Arabidopsis acts as both protein and RNA chaperone to increase tolerance of heat and cold stresses

Abstract: The P3 proteins are plant-specific ribosomal P-proteins; however, their molecular functions have not been characterized. In a screen for components of heat-stable high-molecular weight (HMW) complexes, we isolated the P3 protein AtP3B from heat-treated Arabidopsis suspension cultures. By size-exclusion chromatography (SEC), SDS-PAGE and native PAGE followed by immunoblotting with anti-AtP3B antibody, we showed that AtP3B was stably retained in HMW complexes following heat shock. The level of AtP3B mRNA increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
(127 reference statements)
0
22
0
Order By: Relevance
“…AtP3B -overexpressing transgenic Arabidopsis plants showed enhanced tolerance to heat and low temperature stress, whereas knockdown of AtP3B by RNAi led to increased sensitivity to both stresses [ 36 ]. In the current study, we evaluated the physiological functions of AtP3B using transgenic sweetpotato plants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…AtP3B -overexpressing transgenic Arabidopsis plants showed enhanced tolerance to heat and low temperature stress, whereas knockdown of AtP3B by RNAi led to increased sensitivity to both stresses [ 36 ]. In the current study, we evaluated the physiological functions of AtP3B using transgenic sweetpotato plants.…”
Section: Resultsmentioning
confidence: 99%
“…AtP3B plays an essential role in cold stress tolerance in Arabidopsis , a process mediated by its RNA chaperone activity [ 36 ]. Therefore, we investigated whether the OP plants also exhibited increased tolerance to low temperatures due to AtP3B overexpression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional analysis of DEPs in cantaloupe revealed that proteins involved in ribosomes and protein processing in the endoplasmic reticulum were highly enriched in both cultivars under cold treatment. Numerous studies have indicated that ribosomal proteins [39], endoplasmic reticulum related proteins [40] and molecular chaperones involved in protein folding [41] are essential for protein synthesis, and they have been speculated to play central roles in regulating stress tolerance in plants. In this study, 38 ribosome-related proteins were found in GE after 12 days of cold treatment, of which 21 were down-regulated and three (XP_008447825.1, XP_008447383.1, XP_008453374.1) were up-regulated.…”
Section: Structural Proteinsmentioning
confidence: 99%